2017
DOI: 10.1038/jp.2016.263
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold paralysis in preterm infants: prevalence and analysis of risk factors

Abstract: Given the prevalence of VFP and its associated morbidity, efforts to decrease PDA ligation and invasive ventilation in preterm infants are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…It has been well established in the literature that a weight of less than 1500 grams at the time of PDA ligation is associated with a greater risk of RLN injury. 2,4,6,[9][10][11][12] Our results also demonstrated that a corrected gestational age of less than 30 weeks at time of surgery was associated with an increased risk of LVFP post-op. This finding is consistent with the work of previous authors who suggested that prematurity was a risk factor for LVFP following PDA-ligation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It has been well established in the literature that a weight of less than 1500 grams at the time of PDA ligation is associated with a greater risk of RLN injury. 2,4,6,[9][10][11][12] Our results also demonstrated that a corrected gestational age of less than 30 weeks at time of surgery was associated with an increased risk of LVFP post-op. This finding is consistent with the work of previous authors who suggested that prematurity was a risk factor for LVFP following PDA-ligation.…”
Section: Discussionsupporting
confidence: 71%
“…In particular, young gestational age and low birth weight are independent risk factors for developing LVFP following PDA ligation. [1][2][3][4][5][6] Depending on the extent of injury, LFVP can be a transient condition, but many patients develop lifelong symptoms and complications. 7,8 In recent history, iatrogenic injuries have surpassed congenital anomalies, such as Arnold-Chiari malformation, as the most common cause of vocal fold paralysis among infants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the variability among studies, the lack of demographic information precluded the ability to ensure no differences in baseline characteristics between the cohorts. However, the importance of this limitation is questionable, as factors such as sex and race have not been shown to affect VFI diagnosis or outcomes 6,33 . The lack of follow‐up information in several studies also limited the analysis of resolution rates and especially time to resolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of this limitation is questionable, as factors such as sex and race have not been shown to affect VFI diagnosis or outcomes. 6,33 The lack of follow-up information in several studies also limited the analysis of resolution rates and especially time to resolution. Finally, while not a limitation, this study was not intended to examine what proportion of traumatic births result in VFI.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal cord paralysis (VCP) is a common airway abnormality in neonates in which one or both of the vocal cords are unable to adduct or abduct properly [ 9 ]. It comprises up to 10% of all congenital laryngeal lesions, second only to laryngomalacia, and has been found in 3.5% of preterm infants in the Neonatal ICU, with incidence increasing to 18% in patients born before 26 weeks GA [ 10 , 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%